The Predictive Value of Autoantibody Spectrum on Organ Damage in Patients With Systemic Lupus Erythematosus - Fang YUAN,; Fenghua WEI,; Haiting HUANG,; Yi XUE,; Pengwei GUO,; Yanwu YOU, (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate the positive detection rate and predictive value of autoantibodies, including anti-double stranded deoxyribonucleic acid (anti-dsDNA) antibodies, anti-histone antibodies (AHAs), anti-ribosomal (anti-Rib) P antibodies, anti-Smith (anti-Sm) antibodies, anti-U1 ribonucleoprotein (anti-U1RNP) antibodies, anti-Sjögren’s syndrome type A antibodies and anti-Sjögren’s syndrome type B antibodies, on organ damage in patients with systemic lupus erythematous (SLE). Patients and methods: A total of 225 patients with SLE (37 males, 188 females; mean age 37.4±15.9 years; range, 7 to 80 years) were evaluated retrospectively. Statistical analysis was performed to obtain the positive detection rate of autoantibodies and to investigate the predictive value. Results: There were statistically significant differences of positive anti-dsDNA antibodies in renal damage, photosensitization, hematological abnormalities and serositis (p<0.05) and a statistically significant difference of positive AHAs in photosensitization (p<0.05). There was statistically significant difference of positive anti-U1RNP antibodies in renal damage (p<0.05). There were also statistically significant differences of positive anti-Smith antibodies in renal damage, arthritis, photosensitization, oral ulcers, hematological abnormalities and serositis (p<0.05) and of positive anti-Rib antibodies in renal damage, arthritis, photosensitization, malar rash, hematological abnormalities and serositis (p<0.05). However, there were no statistically significant differences of positive anti-Sjögren’s syndrome type B antibodies and anti-Sjögren’s syndrome type A antibodies in renal damage, arthritis, malar rash, neuropsychiatric disorders, hematological abnormalities and serositis (p>0.05). Conclusion: Autoantibody spectrum is an important serological basis for SLE diagnosis. There are differences in the autoantibodies distribution of SLE patients with different organ damage, suggesting a certain clinical value for prediction of organ damage in SLE.